Success rate of cervical cerclage at Siriraj Hospital - Phanitra Maneeratprasert (2020)
© 2019, Siriraj Medical Journal. Objective: To determine the success rate of cervical cerclage at Siriraj Hospital and the associated factors. Methods: The study included 90 pregnant women who received cervical cerclage procedures at Siriraj Hospital during 2007-2016. Clinical information and the cerclage procedures were evaluated. Successful cervical cerclage was defined as delivery at 34 weeks' gestation or more. Results: The mean maternal age was 31.8 ± 5 years. The most common indication was history of second trimester abortion (76.7%). The mean gestational age (GA) at cervical cerclage was 18.0 ± 4.3 weeks. The mean cervical length was 25.2 ± 12.0 mm. Most of the patients had no cervical dilatation (76.7%). Almost all the cervical cerclage procedures were performed using McDonald's technique (98.9%). Of the 90 women, 66 (73.3%) delivered at > 34 weeks' gestation, while 59.9% delivered at > 37 weeks' gestation. The mean birth weight was 2404.9 ± 991.7 grams. The success rate of cervical cerclage increased significantly among women with greater cervical length (28.2±10.5 vs. 18.0±14.9 mm., p=0.002), without cervical dilatation (83.3% vs. 58.3%, p=0.046), without bulging of membranes (92.5% vs. 66.7%, p=0.002), and prophylactic operations (89.4% vs. 58.3%, p=0.001). Maternal complications were significantly lower in women with successful cervical cerclage (9.1% vs. 45.8%, p < 0.001). Conclusion: The success rate of cervical cerclage at Siriraj Hospital was 73.3%. Possible associated factors included cervical length, cervical dilatation, bulging of membranes, and the prophylactic procedure.